(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
The article examines the mechanisms of attracting investments in the economy of Uzbekistan on the example of free economic zones (FEZs). The analysis of the current state of FEZs, including their achievements and existing problems, is presented. International experience is also studied and recommendations for improving the investment climate are proposed, including modernization of infrastructure, simplification of administrative procedures, development of human capital and attraction of new sources of financing. The implementation of the proposed measures will strengthen Uzbekistan’s position in the global economy.